A Biobased Flame‐Retardant Resin Based on Lignin. (9th August 2017) - Matsushita, Yasuyuki; Hirano, Daisuke; Aoki, Dan; Yagami, Sachie; Takagi, Yasuo; Fukushima, Kazuhiko
Abstract: This study focuses on the development of biobased flame‐retardant resins. Lignin and α, ω‐alkanediols are used, which can be obtained from biomass. To introduce intumescent properties, phosphoryl chloride and 3‐amino‐1, 2, 4‐triazole are introduced into kraft lignin prior to it being resinified with the α, ω‐alkanediols. In simple combustion tests using a gas burner at 1300 °C, the resins prepared exhibit nonburnable properties, producing only a swollen char. According to dynamic mechanical analysis, the glass transition temperature decreases with an increase in the carbon number and amount of the alkanediols introduced. The mechanical loss tangent (tan δ) value of the prepared resins is below 1, indicating that the resins would not drip flaming particles during burning. Indeed, the specimens do not generate particles in the simple combustion tests. According to the results of cone calorimeter testing, the total heat release and the peak heat release rate are significantly smaller than those of a commercial phenol‐formaldehyde‐resin‐containing flame retardant. Abstract : Biobased intumescent flame‐retardant resins are developed based on lignin and α, ω‐alkanediols, which can be obtained from biomass. The resins prepared exhibit nonburnable properties, producing only a swollen char. According to the results of cone calorimeter testing, the total heat release and the peak heat release rate are significantly smaller than those of a commercial phenol‐formaldehyde‐resin‐containing flame retardant.